PENERAPAN METODE AGILE SCRUM DALAM PENGEMBANGAN SISTEM INFORMASI ADMINISTRASI KEGIATAN COASS (CO-ASSISTANT) PADA RUMAH SAKIT PENDIDIKAN GIGI DAN MULUT - I Gusti Ngurah Ari Wira Nugraha; Ngurah Indra ER; Komang Sri Utami; Fajar Purnama; I Wayan Shandyasa (Jurnal SPEKTRUM, 2025)
The manual administration of the Co-Assistant (Coass) program at Dental and Oral Education Hospitals is often inefficient, prone to delays, and lacks transparency in data handling. To address these limitations, this study implemented a web-based information system developed using the Agile Scrum methodology. Development was carried out through five iterative sprints, totaling 106 story points, enabling the team to incrementally build and refine system features in alignment with stakeholder needs. The Scrum approach not only facilitated the completion of the product backlog but also proved instrumental in managing complex business logic and ensuring seamless inter-module integration. Key outcomes include enhanced efficiency in logbook recording, streamlined clinical assessment workflows, and improved data transparency. These results suggest that Agile Scrum is well-suited for dynamic, semi-academic environments such as teaching hospitals. This research offers a replicable, adaptive development model that can guide other health education institutions in accelerating the digital transformation of their academic and clinical administrative processes.